Kirjallisuushistoria tänään - Saariluoma, Liisa (Kirjallisuudentutkijain Seuran vuosikirja, 1989)
English summaries.
Keywords: Brect, Bertold; Bürger, Peter; Fokkema, Douwe; Holsti, Keijo; Tammi, Pekka : Onko tällä tekstillä lukijaa?; Williams, Raymond; 1980-luku; 1980-talet; feminism; feminismi; genrer; genret; keskiaika; kirjallisuudenhistoria; kirjallisuudentutkimus; kirjallisuus; koder; koodit; litteratur; litteraturhistoria; litteraturvetenskap; marxism; marxismi; medeltiden; teoriat; teorier; Finland; Suomi